2009
DOI: 10.1021/la803361y
|View full text |Cite
|
Sign up to set email alerts
|

Effect of Molecular Structure of Cationic Surfactants on Biophysical Interactions of Surfactant-Modified Nanoparticles with a Model Membrane and Cellular Uptake

Abstract: The aim of this study was to test the hypothesis that the molecular structure of cationic surfactants at the nanoparticle (NP)-interface influences the biophysical interactions of NPs with a model membrane and cellular uptake of NPs. Polystyrene NPs (surfactant free, 130 nm) were modified with cationic surfactants. These surfactants were of either dichained (didodecyldimethylammonium bromide [DMAB]) or single chained (cetyltrimethylammonium bromide [CTAB] and dodecyltrimethylammonium bromide [DTAB]) forms, th… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

7
121
0

Year Published

2011
2011
2024
2024

Publication Types

Select...
9
1

Relationship

0
10

Authors

Journals

citations
Cited by 118 publications
(128 citation statements)
references
References 36 publications
7
121
0
Order By: Relevance
“…It has been reported that the sign of surface charges can dramatically influence uptake of GNPs. 32 In addition, different shapes, 2,32 ligand structures, 46 and compositions 32,44 of GNPs can also lead to different degrees of cellular uptake. In particular, it is found that cationic and anionic GNPs follow different internalization pathways to enter cells.…”
Section: The Influence Of Physiochemical Properties To Biological Effmentioning
confidence: 99%
“…It has been reported that the sign of surface charges can dramatically influence uptake of GNPs. 32 In addition, different shapes, 2,32 ligand structures, 46 and compositions 32,44 of GNPs can also lead to different degrees of cellular uptake. In particular, it is found that cationic and anionic GNPs follow different internalization pathways to enter cells.…”
Section: The Influence Of Physiochemical Properties To Biological Effmentioning
confidence: 99%
“…The interfacial properties which influence the interactions in biological environments might be conveniently investigated using simplified models of complex cell membranes [21]. The bilayer [22] or lipid monolayer systems are widely used to characterize quantitatively the membrane affinity of bioactive molecules and reveal the resulting structural changes [23][24][25][26][27]. Nevertheless, the interaction of drug delivery NPs with lipid monolayer is rarely investigated although such studies could be effectively used in developing functionalized nanocarrier systems [2,25,28].…”
Section: Introductionmentioning
confidence: 99%
“…In 18 addition, CLSM images confirmed that the NPs were internalized. 19 Various properties of NPs, particularly the size and charge that most NP platform are normally 20 characterized for, have been shown to affect NP cellular uptake to some extent; however, as noted 21 by [49,50], those properties can hardly be used as reliable predictors, and NP interactions with 22 …”
mentioning
confidence: 99%